2017
DOI: 10.5530/pj.2017.6.130
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Activities of Ethanolic Extract from Mimosa pudica L. in Normal and Streptozotocin-Induced Diabetic Rats

Abstract: Context:Mimosa pudica L. its unique property to collapse when touched and opens up. Aims: To evaluate hypoglycemic and hypolipidemic activities of 80% ethanolic extract from whole plant of Mimosa pudica L. (MPE) by measuring fasting blood glucose in normal and streptozotocin (STZ)-induced diabetic rats treated with MPE. Materials and Methods: An eight-week study using MPE was performed in normal and streptozotocin (STZ)-induced diabetic rats. Hypoglycemic activities in normal and STZ-induced diabetic rats and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Diabetesinduced hyperlipidemia is attributable to excess mobilization of fat from the adipose due to the under utilization of glucose [44]. According to studies by [45,46,47] it was shown that chronic insulin deficiency as observed in alloxan-induced hyperglycaemia in experimental animals is associated with diminished levels of LDL receptors, blood cholesterol and triglyceride [48,49]. This results to an increase in LDL particles and consequently increases serum level of LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetesinduced hyperlipidemia is attributable to excess mobilization of fat from the adipose due to the under utilization of glucose [44]. According to studies by [45,46,47] it was shown that chronic insulin deficiency as observed in alloxan-induced hyperglycaemia in experimental animals is associated with diminished levels of LDL receptors, blood cholesterol and triglyceride [48,49]. This results to an increase in LDL particles and consequently increases serum level of LDL.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment lasted for eight weeks, blood serum was collected, and biochemical parameters were analysed. The group which received M. pudica extracts tend to have a high level of HDL and TG, TC and LDL decrease which shows the hypolipidemic potential of M. pudica [34].…”
Section: Hypolipidemic Activitymentioning
confidence: 93%
“…Ethanolic plant extracts were reported to reduce the blood glucose level in streptozotocin-induced diabetic rats. This indicates that Mimosa pudica has a significant antidiabetic activity 20 . Chloroform and methanolic root, shoot extracts showed wound healing activity when applied topically with a significant increase in the hydroxyproline content, tear strength and dry weight of the granulation tissue in the wound incision pattern 21 -23 .…”
mentioning
confidence: 94%